EDUKASI HIPERTENSI BAGI JEMAAT GKI TERATE - Chris, Arlends; Djaja Saputera, Monica (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
In 2023, WHO shows that 1.28 billion people in the world suffer from hypertension. 2018 Riskesdas data shows that prevalence of hypertension in Indonesia reached 34.1%, and data from the Indonesian Ministry of Health shows that prevalence of hypertension in Jakarta Capital Special Region reached 33.4%. Hypertension is a non-communicable disease (NCD) that continues to increase in developed and developing countries, including Indonesia. This community service program aims to educate the congregation about hypertension at GKI Terate, West Jakarta. Through this activity, the congregation at GKI Terate is expected to take promotive and preventive measures for hypertension. Thus, this activity can help fulfill the SDGs target in Indonesia, significantly reducing premature death rates due to non-communicable diseases. The methods used are anthropometric measurements, short interviews, education, and knowledge tests. The results of hypertension education activities which were measured through pre-test and post-test using statistical calculations did not show significant differences in knowledge. Although the results did not show a difference in knowledge scores, there was an increase in the range of knowledge scores on hypertension. In general, the knowledge of the GKI Terate congregation regarding the topic of hypertension is in the reasonably good category. Follow-up efforts still need to be carried out through regular education to increase promotive and preventive measures to control hypertension in the future.